44.6k views
4 votes
What is the value of n. 6(x – 1) = 9(x + 2)

2 Answers

6 votes

Answer:

x=−8

Explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

6*(x-1)-(9*(x+2))=0

(6 • (x - 1)) - 9 • (x + 2) = 0

6 • (x - 1) - 9 • (x + 2) = 0

Pull out like factors :

-3x - 24 = -3 • (x + 8)

-3 • (x + 8) = 0

Solve : -3 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solve : x+8 = 0

Subtract 8 from both sides of the equation :

x = -8

User Eugen Dubrovin
by
5.0k points
3 votes

6(x-1) = 9(x+2)

Use distributive property on both sides:

6x-6 = 9x + 18

Subtract 6x from both sides:

-6 = 3x + 18

Subtract 18 from both sides:

-24 = 3x

Divide both sides by 3:

X = -8

User Matheeeny
by
4.7k points